The IIR evaluation model: a framework for evaluation of interactive information retrieval systems - Borlund Pia (Information Research: An International Electronic Journal)
An alternative approach to evaluation of interactive information retrieval (IIR) systems is proposed. The model provides a framework for the collection and analysis of IR interaction data.